Improvement of Community Economic Independence Through Sharia Micro Financial Institution in Padamulya Village, Pasirkuda Cianjur District - D. Moch Lukman Nurkarim; Afiatin Dewi (Journal of Islamic Economy and Community Engagement, 2022)
Lack of public understanding of Islamic economic principles is one of the reasons people use conventional financial services institutions. And the existence of official financial institutions and based on sharia is very far from the residence of the Padamulya Village community. The solution to the problem is firstly by providing understanding to the public about the principles and values of Islamic economics, so that the community is able to economically in accordance with the provisions of religion and aware of the dangers of usury. Secondly, by presenting financial institutions that are official and in accordance with Islamic economic principles, so that people will be easier when they will save money from their agricultural products and help people who have Micro and Small Business. The output target that the author made was in the form of making an article entitled "Increasing Community Economic Independence through the Initiation of Sharia Microfinance Institutions in Padamulya Village, Pasirkuda District, Cianjur Regency". The result of the LKMS Initiation program was the establishment of Padamulya BMT located in Padamulya Village, Pasirkuda District, Cianjur Regency. The BMT can be utilized by the people of Padamulya Village to use Islamic financial services such as savings, financing and ZISWAF management that can help the economy of the middle and lower classes.Keywords: Economic independence, LKMS initiation.